Der Herrscher als Pilger im westlichen und östlichen Mittelalter –: eine Skizze - Kolditz, Sebastian (Comparativ, 2008)
Investigating medieval royal pilgrimage from a comparative perspective, certain characteristics can be observed: Byzantine emperors normally did not go on pilgrimage, preferring to collect holy relics in their capital. In the West, royal pilgrimage flourished especially during the Later Middle Ages, playing a key role in the practice of rulership, without, however, making a significant contribution to the sacral character of monarchy. Christian kings seldom crossed the borders of their realms to visit sacred places. Muslim rulers (apart from the early caliphs) followed a similar pattern, often avoiding to perform the hajj to Mecca personally. Instead, royal pilgrimage over long distances was a significant phenomenon at the periphery of both religious spheres: in West Africa and Scandinavia.